The Correlation Between Students’ Interest and Their Achievement in Writing Recount Text at SMKN 2 Boyolangu Tulungagung in Academic Year 2019/2020 - Elisabeth Wanodyayu Puji Christanti; Dina Kartikawati (STKIP PGRI Trenggalek, 2021)
This research is aimed to find out the correlation between students’ interest and their achievement in writing at SMKN 2 Boyolangu Tulungagung. The problem needs to be discussed in this research is whether there is a correlation between students’ interest and their achievement in writing at SMKN 2 Boyolangu Tulungagung. This research was quantitative research that used the correlation method. It was conducted at SMKN 2 Boyolangu Tulungagung. The population was all of the students at SMKN 2 Boyolangu Tulungagung in the academic year of 2019/2020 which was 2.250 students. The researcher used purposive sampling to choose the sample. There were 34 students chosen from X Tata Kecantikan 4 as the sample of this research. The instruments of the research were questionnaire which was related to the students’ interest and documentation of their writing achievement which assessed by using Pearson Product Moment’s formula that was analyzed by using the SPSS 23 statistics program. The result of the research showed that there is a significant relationship between students’ interest and their writing achievement. It can be proved from value sig. (2 tailed) sig. (2-tailed) of 0.000 is lower than 0.05. Moreover, the correlation coefficient value is 0.838 it means there is a very strong positive correlation. Based on the result of the research, it can be concluded that students’ interest contributes to their writing achievement